Anxiety, emotional regulation and concentration during a 35-day bed rest - Dolenc, Petra (Array, 2008)
Summary: The psychological condition of astronauts is an important factor contributing to mission success in limited space. Bed rest is a well-accepted method by which an acute stage of human adaptation to weightlessness in space flights is simulated, as well as an important model to study consequences of physical inactivity and sedentary inactivity on human body. The objective of the study was to investigate anxiety level, concentration, as well as emotional regulation and control in ten young male subjects during a 35-day horizontal bed rest. Participants were asked to complete psychometric inventories before, during and after bed rest. The results have shown that a prolonged period of bed rest did not result in greater anxiety levels nor poorer emotional regulation and control. Likewise, concentration expressed as the quantity of performance was not impeded, whereas concentration expressed as the quality of performance improved after the bed rest experiment. The objective of this research was to provide evidence that the provision of favourable habitability countermeasures can prevent deterioration in the psychological state under conditions of physical immobilisation. Our findings have applied value in the field of health prevention and rehabilitation